Resistance of rice accessions against rice yellow stem borer, Scirpophaga incertulas (Walker) under greenhouse and field conditions - Amsagowri, V; Muthukrishnan, N; Muthiah, C; Mohankumar, S (ORYZA-An International Journal of Rice, 2021)
Sixteen rice accessions were screened under greenhouse condition and field condition against yellow stem borer (YSB) during 2014-15. Six wild accessions were screened against YSB under green house condition only. In green house condition, the accessions viz., Oryza minuta, O. nivara, IR 20, IET 23710 and IET 23715 recorded the score of 3 (moderately resistant) at both phases. Under field condition, the variety TKM 6 recorded score 1 (resistant) based on Â dead heart and white ear damage followed by IR 20, IET 23710 and IET 23715, which recorded the score of 3 (moderately resistant) for both dead heart and white ear damage. Both under field and green house condition, IR 20, IET 23710 and IET 23715 showed moderate resistance to yellow stem borer.